Strain-hardening Ultra-High-Performance Geopolymer Concrete (UHPGC): Matrix design and effect of steel fibers. (February 2022) - Lao, Jian-Cong; Xu, Ling-Yu; Huang, Bo-Tao; Dai, Jian-Guo; Shah, Surendra P.
Abstract: Ultra-High-Performance Geopolymer Concrete (UHPGC) is an emerging greener ultra-high-performance concrete (UHPC). In this study, strain-hardening UHPGC was designed and developed for the first time, and a compressive strength of 222 MPa was achieved. Straight steel fibers were used as the reinforcement and significant tensile strain hardening was observed for all the UHPGC mixtures developed in this study. It was found that the tensile strength of UHPGC increased with the fly ash-to-slag ratio as well as the steel fiber content. By altering the fly ash-to-slag ratios and steel fiber dosages, the tensile ductility varied within the range of 0.35%–0.55%, and the residual crack width after the tensile test was approximately 10–20 μm only. The SEM observation of the pull-out fiber surface confirmed an excellent bond between the UHPGC matrix and steel fiber. The findings of this study have laid down a useful basis for designing and developing UHPGC materials with the tensile strain hardening behavior. Graphical abstract: Image 1 Highlights: Strain-hardening UHPGC was designed and developed for the first time. The compressive strength of UHPGC was 163–222 MPa, and the tensile strain capacity was 0.35–0.55%. The residual crack width of UHPGC after the tensile test was approximately 10–20 μm only. A very dense microstructure of UHPGC matrix was observed through the BSE analysis.